2020
DOI: 10.1155/2020/5174656
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Contraceptive Use and Its Determinants in Ethiopia: A Systematic Review and Meta-analysis

Abstract: Background. Postpartum contraceptive use is defined as the avoidance of short spaced pregnancies and unintended pregnancy through the first 12 months after delivery. In Ethiopia, different studies have been conducted to assess the prevalence of postpartum contraceptive use and associated factors. The findings of these studies were inconsistent and characterized by great variability. Therefore, the aim of this systematic review and meta-analysis was to estimate the pooled prevalence of postpartum contraceptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…The discrepancy may be due to cultural influences and the relatively high unmet need for family planning in Ethiopia [ 5 ]. The present finding is comparable to a study finding from Ethiopia(48.11%) [ 17 ] and Rwanda (51.1%) [ 43 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The discrepancy may be due to cultural influences and the relatively high unmet need for family planning in Ethiopia [ 5 ]. The present finding is comparable to a study finding from Ethiopia(48.11%) [ 17 ] and Rwanda (51.1%) [ 43 ].…”
Section: Discussionsupporting
confidence: 89%
“…The magnitude of postpartum modern contraception utilization in Ethiopia ranges from 12.05% to 80.32% [14,15]. Different studies found antenatal care, postnatal care, resumed sexual activity, partner approval for contraceptive use, menses return, and counseling on family planning use as determinants of postpartum modern contraception use [15][16][17][18][19][20].…”
Section: Plos Onementioning
confidence: 99%
“…The single population proportion formula was used to calculate the sample size with the following assumption. The proportion of postpartum women who utilized postpartum family planning which was 48.11% was taken [ 10 ]. The marginal error of 4%, design effect 1.5, and 95% confidence level.…”
Section: Methodsmentioning
confidence: 99%
“…Data were collected by 25 data collectors who know Afan Oromo and Amharic. The quantitative data were collected through interviewer-administered interviews using adopted questionnaires from reviewed literature on postpartum family planning [ 3 , 10 – 25 ]. Inorder to minimize potential bias, the authors used precise tools and well trained female BSC nurses,who were not working in the same facility/study area, for data collection.…”
Section: Methodsmentioning
confidence: 99%
“…A recent systematic review and meta-analysis found that postpartum family planning uptake in Ethiopia is low compared to the existing global recommendations on postpartum contraceptive use. Resumption of sexual activity, having received antenatal care, maternal education above or equal to secondary school, postnatal care with family planning counselling, resumption of menses, and being ≥ 6 months postpartum were found to be significantly associated with postpartum contraceptive use [ 12 ].…”
Section: Introductionmentioning
confidence: 99%